Pengaruh Kebisingan Dan Masa Kerja Terhadap Stres Kerja Pegawai Negeri Sipil BKPSDM Kota Pariaman - Alfian Alfian; Putri Rahayu Gian (JURNAL PUNDI, 2020)
Fast traslate Icon translate     Fast traslate Icon translate This study aims to analyze the effect of noise and work time on work stress on civil servants working at BKPSDM  Pariaman City. This study includes quantitative research. This research population is all civil servants who work at BKPSDM Pariaman City. Sampling method using census. Then choose a sample size of 33 people. The analysis technique used is multiple regression analysis using SPSS version 16.0. The results based on multiple regression analysis show that noise does not significantly influence work stress that occurs in civil servants working at BKPSDM Pariaman City. This supports the results of previous studies conducted by Lathifa Rusyda Gani, Dwita Aryadina, Laksmi Indreswari and Alif Mardijana (2005) who stated that noise had no significant effect on work stress at a significant level of 0.654. . In addition, the period of work has a significant effect on work stress that occurs in civil servants who work in BKPSDM Pariaman CityKeyword : Noise, Work Time, Work Stress